Removal Of Hydrogen Sulfide From Biogas Using Ceo2 Naoh Psac Synthesis And Performance From Laboratory Scale To Scale Up Process Design - Lau, Lee Chung (2015)
In this study, CeO2/NaOH/PSAC sorbent was successfully synthesized and applied in hydrogen sulfide removal from biogas. Preliminary study showed that the best synthesis route was using soaking method to impregnate cerium oxide and sodium hydroxide onto palm shell activated carbon (PSAC). In addition, calcination must be applied as final step of the preparation because it increased the sorption capacity. Preparation parameters studied were impregnation time (0 – 180 min), cerium amount (1 – 10% wt Ce), sodium hydroxide concentration (0.2 – 1.0M NaOH), calcination temperature (250 – 500oC) and duration (1 – 4 hours). Optimization of sorbent preparation parameters was successful and the optimum values were 1.5 hours impregnation time, 5 wt% cerium, 1.0 M NaOH, 400oC calcination temperature and 3 hours of calcination time. Operating parameters that were found to affect the sorption capacity were sorption temperature, H2S concentration, sorbent amount, and flow rate. Maximum value of sorption capacity can be identified for each of these operating parameters. Moreover, other gas components such as water, carbon dioxide and methane can also affect the sorption capacity differently. Data analysis showed that Freundlich sorption isotherm can best described the sorption behavior. Thermodynamic study showed that enthalpy change (ΔH) and entropy change (ΔS) were calculated to be –6.0 kJ/mol and 25.7 J/mol.K. The sorption was pseudo–second order with activation energy 11.7 kJ/mol and rate constant was between 2.387–4.066 X 10-6 g/mg.min for temperature 30–70oC. Breakthrough curve was fitted well by using breakthrough model developed by Chu (2004). Up to 78% of original sorption capacity was achieved in the regeneration study using heat treatment under inert atmosphere. The regeneration temperature and time were 500oC and 4 hours, respectively. Scale up sorption process using the developed CeO2/NaOH/PSAC sorbent was successfully designed with a rate of return (ROR) of two years. Simulation study was also performed and increased efficiency at higher flow rate and smaller sorption column was discovered.